2017
DOI: 10.1002/jmv.24826
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nucleoside‐sparing regimen based on raltegravir and ritonavir‐boosted darunavir in HIV‐1‐infected treatment‐experienced patients

Abstract: Dual therapy was effective and safe for the vast majority of antiretroviral-experienced subjects. Such therapy can be recommended especially for patients with renal impairment or NRTIs intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Specific antiviral drugs for a range of viral infections are lacking and systemic supportive therapy and symptomatic treatment remain the mainstays. Nucleoside drugs were the earliest clinically used antivirals, but the side-effects associated with these drugs, including acute renal failure, increase with increasing drug doses [90]. New and effective agents are therefore urgently required.…”
Section: Classical Activities Of Fucoidanmentioning
confidence: 99%
“…Specific antiviral drugs for a range of viral infections are lacking and systemic supportive therapy and symptomatic treatment remain the mainstays. Nucleoside drugs were the earliest clinically used antivirals, but the side-effects associated with these drugs, including acute renal failure, increase with increasing drug doses [90]. New and effective agents are therefore urgently required.…”
Section: Classical Activities Of Fucoidanmentioning
confidence: 99%
“…This expressed our expectation that any difference in effectiveness between the two regimens would not be dramatic but within this interval. Second, we reviewed studies where patients switched onto the alternative regimens (boosted darunavir with lamivudine or emtricitabine [2326], raltegravir with boosted darunavir [2729]). Based on these studies, we expected a failure rate of approximately 10 failures per 100 patient-years on each control regimen.…”
Section: Methodsmentioning
confidence: 99%
“…An observational study evaluating 121 patients treated with RAL combined with PI, reported that approximately 70% of them remained on this regimen with a median treatment duration of 60 months, with treatment simplification being the main reason for 2DR discontinuation in half the 2DR-failing patients [26]. Moreover, only three patients out of 81 (3.7%) who were switched to RAL/DRV/r experienced a virological failure [27]. Indeed, in our cohort, of 54 patients switching to a 2DR combining PI and INSTI, three (5.5%) featured a virological failure, and were switched back to 3DR, while 18 patients were switched to a second line 2DR, mainly due to a need for treatment simplification and 62.9% patients were maintained on PI +INSTI.…”
Section: Plos Onementioning
confidence: 99%